Causalidad temporal entre producto y exportaciones para Colombia: análisis sectorial - Rendón Vallejo, Lina Viviana (Sociedad y Economía, 2007)
This paper inquires about the relationship between gross domestic product and exporta inColombia, The analysis yields that both manufacturing exports and primary exports, differentto agroindustrial and cofiee exports, cause the product á la Granger, given support to thehypothesís of growth through increments of thosc exports.